2019
DOI: 10.1021/acsami.8b18523
|View full text |Cite
|
Sign up to set email alerts
|

Micro-/Nanoscale Approach for Studying Scale Formation and Developing Scale-Resistant Surfaces

Abstract: Blockage of pipelines due to accretion of salt particles is detrimental in desalination and water-harvesting industries as they compromise productivity, while increasing maintenance costs. We present a micro-/nanoscale approach to study fundamentals of scale formation, deposition, and adhesion to engineered surfaces with a wide range of surface energies fabricated using the initiated chemical vapor deposition method. Silicon wafers and steel substrates are coated with poly(1H,1H,2H,2H-perfluorodecylacrylate) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 42 publications
0
33
2
Order By: Relevance
“…Another type of vapor deposition is called CVD. This process undergoes a high vacuum and is widely used in the semiconductors industry providing a solid, high quality, and a high resistance coating layer on any substrate [19][20][21][22]. CVD can be used for mechanical parts in constant contact, which need protection against corrosion and wear.…”
Section: Chemical Vapor Deposition (Cvd) Coatingmentioning
confidence: 99%
“…Another type of vapor deposition is called CVD. This process undergoes a high vacuum and is widely used in the semiconductors industry providing a solid, high quality, and a high resistance coating layer on any substrate [19][20][21][22]. CVD can be used for mechanical parts in constant contact, which need protection against corrosion and wear.…”
Section: Chemical Vapor Deposition (Cvd) Coatingmentioning
confidence: 99%
“…For example, by using gold‐coated Si 3 N 4 tips modified with various thiol molecules (Figure C), the mean adhesion force between Au:S(CH 2 ) 10 COO − modified tip and calcium oxalate monohydrate with exposed (100) crystal face was 4.28 ± 0.62 nN, which was approximately five times of the value for Au:S(CH 2 ) 10 CH 2 OH (0.83 ± 0.33 nN) and Au:S(CH 2 ) 10 CH 3 (0.66 ± 0.17 nN). On the other, to study their adhesion strength, the shaped particles of crystals (e.g., CaSO 4 ·2H 2 O) were adhered to a tipless cantilever beam using a micromanipulator setup (Figure D) . For example, Gleason observed that polymer coatings with lower polar components of surface energies exhibited lower adhesion strengths.…”
Section: The Mechanism Of Scale Formationmentioning
confidence: 99%
“…For example, Gleason observed that polymer coatings with lower polar components of surface energies exhibited lower adhesion strengths. Compared with polymer coatings such as poly(1,3,5,7‐tetravinyl‐1,3,5,7‐tetrame‐thylcyclotetrasilohexane) (pV 3 D 3 ), poly(tetravinyl‐tetrame‐thylcyclotetrasilohexane) (pV 4 D 4 ), poly(divinylbenzene) (pDVB), and copolymer of poly(2‐hydroxyethylmethacrylate) and polyethylene glycol diacrylate (pHEMA‐co‐pEGDA), poly(1 H ,1 H ,2 H ,2 H ‐perfluorodecyl acrylate) (pPFDA)‐coated substrates showed the lowest salt adhesion forces of 11.1 ± 1.6 and 6.0 ± 2.75 nN in dry and wet states, respectively . This result indicates the effect of polar components of surface energies on developing efficient scale‐resistant engineered surfaces.…”
Section: The Mechanism Of Scale Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The pipe scale formation is considered as a joint reaction between the leachate and piping materials [ 5 ]. To mitigate clogging consequences, conventional engineering measures have mainly focused on pipe cleaning, including aeration in the pipeline [ 6 ], adjustment of hydraulic loading [ 7 ], high-pressure water jetting [ 8 ], addition of scale inhibitors [ 9 ], etc.…”
Section: Introductionmentioning
confidence: 99%